Tissue valves are preferable for patients with end‐stage renal disease: an aggregate meta‐analysis. Issue 8 (8th July 2016) - Altarabsheh, Salah E.; Deo, Salil V.; Dunlay, Shannon M.; Obeidat, Yaqthan M.; Erwin, Patricia J.; Rababa'h, Abeer; Sarabhu, Nagaraju; Navale, Suparna; Cho, Yang Hyun; Lamba, Harveen K.; Markowitz, Alan H.; Park, Soon J.
Abstract: BACKGROUND: Valve selection in patients with end‐stage renal disease (ESRD) is uncertain. We performed a systematic review and meta‐analysis to compare clinical outcome in ESRD patients undergoing valve replacement. METHODS: We systematically searched multiple databases (2000–October 2015) to identify original studies comparing adverse events between mechanical and biological valve replacement in ESRD patients. End‐points studied were: postoperative mortality, bleeding events, need for re‐operation, and late survival. A random‐effect inverse‐variance weighted analysis was performed; event rates are compared as odds ratio (OR and 95% confidence interval) and hazard ratios (HR) for time‐to‐event data. Mechanical valve and tissue valve replacement were considered as study and control cohorts, respectively. RESULTS: Fifteen retrospective studies (5523 mechanical and 1600 tissue valve) were included in our meta‐analysis. Early mortality was comparable (OR 1.15 [0.77; 1.72]; p = 0.49). The mean follow‐up among studies ranged from 1.6–15 years. Bleeding was significantly higher after mechanical valve replacement (OR 2.55 [1.53; 4.26]; p = 0.0003). Structural valve degeneration was present in only 0.6% patients after a tissue valve replacement. Overall survival after valve replacement was poor (median 2.61 years); valve choice did not influence this outcome (pooled HR 0.87 [0.73; 1.04]; p = 0.14). CONCLUSION: Operative mortality in ESRD patients is comparable between mechanical and tissue valve replacement. Major bleeding episodes are significantly higher after mechanical valve replacement but structural degeneration in tissue valves during the follow‐up period is low. Based on the findings from this meta‐analysis, we would recommend using tissue valves in patients with ESRD.